2022
DOI: 10.1093/jamia/ocac220
|View full text |Cite
|
Sign up to set email alerts
|

Using automated methods to detect safety problems with health information technology: a scoping review

Abstract: Objective To summarize the research literature evaluating automated methods for early detection of safety problems with health information technology (HIT). Materials and Methods We searched bibliographic databases including MEDLINE, ACM Digital, Embase, CINAHL Complete, PsycINFO, and Web of Science from January 2010 to June 2021 for studies evaluating the performance of automated methods to detect HIT problems. HIT problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Medication error–related events constitute the most frequently reported because it is particularly likely to be discovered by error detection algorithms in hospital information systems, 25 which may explain why such events did not exhibit a significant decreasing trend. However, the automation of drug prescription and delivery has the potential to further reduce medication errors, 25,26 as evidenced by the severity of medication errors becoming milder in recent years. Similar to this study’s findings, a 2022 report from the Office of the Inspector General found medication events as the most common type 27 and another study adopting the Medicare Patient Safety Monitoring System found a large reduction in its rate 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Medication error–related events constitute the most frequently reported because it is particularly likely to be discovered by error detection algorithms in hospital information systems, 25 which may explain why such events did not exhibit a significant decreasing trend. However, the automation of drug prescription and delivery has the potential to further reduce medication errors, 25,26 as evidenced by the severity of medication errors becoming milder in recent years. Similar to this study’s findings, a 2022 report from the Office of the Inspector General found medication events as the most common type 27 and another study adopting the Medicare Patient Safety Monitoring System found a large reduction in its rate 28 .…”
Section: Discussionmentioning
confidence: 99%